Effective Strategies In Occupational Safety And Health Management To Increase Employee Productivity - Surbakti, Brian Bastanta; Arifin, Daud (Universitas Dehasen Bengkulu, 2025)
Occupational Safety and Health (OHS) is a crucial aspect in creating a safe, healthy, and productive work environment. This study aims to identify and analyze effective OHS management strategies for improving employee productivity in the manufacturing industry. A quantitative approach was used, distributing questionnaires to 100 respondents working in a medium-sized manufacturing company. Data were analyzed using multiple linear regression to examine the influence of various OHS strategy variables, such as safety training, risk communication, management involvement, and the implementation of standard work procedures, on employee productivity levels.The results indicate that regular safety training and open risk communication significantly influence productivity increases. Furthermore, management involvement in the implementation of OHS programs has been shown to strengthen the company's safety culture. Consistent implementation of work procedures also minimizes workplace accidents and downtime. This study confirms that a planned, structured, and integrated OHS management strategy positively contributes to employee performance, both in terms of work efficiency and motivation.The implications of these findings underscore the importance of a company's commitment to implementing a sustainable OHS management system. Recommendations are given for companies to continue strengthening training, improving internal communication, and increasing the active role of leaders in K3 supervision to create a work environment that supports optimal productivity.